Impact of Pump Speed on Hemodynamics With Exercise in Continuous Flow Ventricular Assist Device Patients. Issue 2 (February 2020) - Lai, Jacqueline V.; Muthiah, Kavitha; Robson, Desiree; Prichard, Ros; Walker, Robyn; Pin Lim, Choon; Wang, Louis W.; Macdonald, Peter S.; Jansz, Paul; Hayward, Christopher S.
Abstract : At fixed speed, the spontaneous increase in pump flow accompanying exercise in patients with continuous flow left ventricular assist devices (cfLVADs) is slight in comparison to normal physiologic response, limiting exercise capacity. We systematically exercised 14 patients implanted with an isolated HeartWare HVAD undergoing routine right heart catheterization at baseline and at maximal safe pump speed. In addition to hemodynamics, mixed venous oxygen saturation (SvO2 ), echocardiography and noninvasive mean arterial pressure, and heart rate were measured. Significantly greater pump flows were achieved with maximum pump speed compared with baseline speed at rest (mean ± standard deviation [SD]: 5.0 ± 0.7 vs. 4.6 ± 0.8 L/min) and peak exercise (6.7 ± 1.0 vs. 5.9 ± 0.9 L/min, p = 0.001). Pulmonary capillary wedge pressure was significantly reduced with maximum pump speed compared to baseline pump speed at rest (10 ± 4 vs. 15 ± 5 mmHg, p < 0.001) and peak exercise (27 ± 8 vs. 30 ± 8 mmHg, p = 0.002). Mixed venous oxygen saturation decreased with exercise ( p < 0.001) but was unaffected by changes in pump speed. In summary, although higher pump speeds synergistically augment the increase in pump flow associated with exercise and blunt the exercise-induced rise in left heart filling pressures, elevated filling pressures and markedly diminished SvO2 persist at maximal safe pump speed, suggesting that physiologic flow increases are not met by isolated cfLVADs in the supported failing heart. Abstract : Supplemental Digital Content is available in the text.